PENULISAN ABSTRAK DALAM ARTIKEL ILMIAH - Salbiah, Siti; Hayadi, B. Herawan; Ningsih, Devi Sri Cahya; Mahar, Tubagus; Rukiyah, Rukiyah; Tresna, Popy Wulandari (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
An abstract is a crucial part of writing a scientific article because it serves as a concise summary explaining the core of the research. Through an abstract, readers can understand the objectives, methods, and main findings of the research without having to read the entire article. This study aims to examine the concept, structure, and principles of effective abstract writing in scientific articles. The method used was a literature review, analyzing various scientific journals that discuss the structure and function of abstracts in academic publications. The results of the study indicate that a good abstract generally contains five main components: research background, research objectives, research methods, research results, and a brief conclusion. This structure helps readers obtain a clear picture of the research's contribution. Furthermore, abstracts should be written concisely, informatively, and using easy-to-understand language. Systematic abstract writing not only improves the quality of scientific articles but also facilitates indexing and searching in scientific databases. Therefore, the ability to write abstracts effectively is a crucial skill for writers in producing quality scientific publications.